Changes in the metabolites of cerebrospinal fluid induced by rTMS in treatment-resistant depression: A pilot study. (July 2022) - Tateishi, Hiroshi; Setoyama, Daiki; Kato, Takahiro A; Kang, Dongchon; Matsushima, Jun; Nogami, Kojiro; Mawatari, Seiji; Kojima, Ryohei; Fujii, Yuka; Sakemura, Yuta; Shiraishi, Takumi; Imamura, Yoshiomi; et al.
Highlights: Metabolomics of repetitive transcranial magnetic stimulation (rTMS) for depression. Analysis of changes in 72 metabolites of cerebrospinal fluid (CSF) by rTMS. rTMS significantly increased CSF niacinamide, kynurenine, and creatinine levels. rTMS significantly decreased CSF cystine levels. Abstract: Repetitive transcranial magnetic stimulation (rTMS) improves depressive symptoms in treatment-resistant depression (TRD). This study aimed to analyze changes in cerebrospinal fluid (CSF) metabolites in patients with TRD after rTMS. Five patients with TRD were enrolled in a high frequency (10-Hz) rTMS study. The concentration of 72 CSF metabolites were measured at baseline and at the end of the 6-week rTMS treatment. rTMS significantly increased CSF niacinamide, kynurenine, and creatinine levels and significantly decreased CSF cystine levels, but not the levels of the other 68 CSF metabolites. This is the first CSF metabolomics study on patients with TRD who underwent rTMS.